Effect of clipping and filtering technique on the performance of OFDM system for different M-QAM - Aswad, Fadhil M.; Jawad,, Mohammed S; Ho, Yih Hwa (AENSI Publisher, 2015)
Orthogonal frequency division multiplexing (OFDM) is a multicarrier modulation technique. OFDM provides high bandwidth efficiency because the carriers are orthogonal to each other and multiple carriers share the data among themselves. The main advantage of this transmission technique is their robustness to channel fading in wireless communication environment. The main aim of this paper is to evaluate the performance of OFDM system after appending clipping and filtering method to reduce high peak-to-average power ratio (PAPR) for different M-QAM. The purpose here to give an idea of what is an OFDM system, how to reduce high peak to average power ratio (PAPR), evaluate system performance after reducing method, its implementation and the analysis of the obtained results of the simulation testing. This OFDM system is able to support different M-QAM modulation schemes. All the different OFDM basic system blocks are introduced in this paper. However, special attention is paid to the processing block of the OFDM system, composed by the Fast Fourier Transform (FFT) block and the Inverse Fast Fourier Transform (IFFT). These blocks are introduced theoretically, to know what is behind them, and also is shown the implementation and simulation of each block. The M-QAM modulation schemes used for the multicarrier OFDM Tx/Rx subsystem are basically 16-QAM, 32-QAM and 64-QAM modulations. Simulation results are provided within this paper. Simulation results have been obtained through the MATLAB tools. Experimental results were obtained by transmitting and receiving an M-QAM OFDM signal through a typical radio frequency (RF). The simulation results are the theoretically expected, showing a perfect match between the OFDM Tx/Rx. However, simulation results have been shown how critical is to adjust the delays in the Rx in order to recover the transmitted signal properly.